A Study of the effect of Porous Silicon Nanoparticles on Human Blood Components (Journal of the College of Basic Education, 2022)
The present work demonstrates the toxicity effect of( PSNPs( on blood components which are prepared by electrochemical etching and plus laser ablation (PLA) Nd: YAG laser method. We conformed the synthesis of porous silicon nanoparticles by using structures and optical properties through measuring absorbance of color and scanning electron microscope techniques. The study of toxicity effect of these nanoparticles on the blood human parameters (in vitro) used complete blood count (CBC). The results of hematology parameter (HCT-PCV); (PLT); (HGB –Hb); (RBCs); (WBCs); Count type white blood cells)are compared with the control groups, Our results shows no significant differences in levels (HCT-PCV); (PLT); (HGB –Hb) ; (RBCs); (WBCs); Count type white blood cells) between the test groups when compared with control groups. This result that there indicates no toxic effect of porous silicon nanoparticles in hematology parameter) in vitro).